Immune Activation Induces Telomeric DNA Damage and Promotes Short‐Lived Effector T Cell Differentiation in Chronic HCV Infection. Issue 5 (25th August 2021) - Nguyen, Lam Nhat; Nguyen, Lam Ngoc Thao; Zhao, Juan; Schank, Madison; Dang, Xindi; Cao, Dechao; Khanal, Sushant; Thakuri, Bal Krishna Chand; Zhang, Jinyu; Lu, Zeyuan; Wu, Xiao Y.; El Gazzar, Mohamed; et al.
Abstract : Background and Aims: Hepatitis C virus (HCV) leads to a high rate of chronic infection and T cell dysfunction. Although it is well known that chronic antigenic stimulation is a driving force for impaired T cell functions, the precise mechanisms underlying immune activation–induced T cell dysfunctions during HCV infection remain elusive. Approach and Results: Here, we demonstrated that circulating CD4 + T cells from patients who are chronically HCV‐infected exhibit an immune activation status, as evidenced by the overexpression of cell activation markers human leukocyte antigen‐antigen D‐related, glucose transporter 1, granzyme B, and the short‐lived effector marker CD127 ‐ killer cell lectin‐like receptor G1 + . In contrast, the expression of stem cell–like transcription factor T cell factor 1 and telomeric repeat‐binding factor 2 (TRF2) are significantly reduced in CD4 + T cells from patients who are chronically HCV‐infected compared with healthy participants (HP). Mechanistic studies revealed that CD4 + T cells from participants with HCV exhibit phosphoinositide 3‐kinase/Akt/mammalian target of rapamycin signaling hyperactivation on T cell receptor stimulation, promoting proinflammatory effector cell differentiation, telomeric DNA damage, and cellular apoptosis. Inhibition of Akt signaling during T cell activation preserved the precursor memory cell population and prevented inflammatory effector cell expansion, DNA damage, and apoptotic death. Moreover, knockdown of TRF2 reduced HP T cell stemness and triggered telomeric DNA damage and cellular apoptosis, whereas overexpression of TRF2 in CD4 T cells prevented telomeric DNA damage. Conclusions: These results suggest that modulation of immune activation through inhibiting Akt signaling and protecting telomeres through enhancing TRF2 expression may open therapeutic strategies to fine tune the adaptive immune responses in the setting of persistent immune activation and inflammation during chronic HCV infection.